The Capitalist Development of the Economy and the Structure of Financial Institutions - Hyman P. Minsky (Levy Economics Institute of Bard College, 1992)
This paper evolves from the sharp contrast in Smithian and Keynesian views about the relationship between the financial structure and the economy. The Smithian perspective implies that the financial structure is irrelevant, whereas the Keynesian position concludes that effective financing is necessary for the "capital development of the economy"- there is also a need to constrain any tendency of what Keynes referred to as speculation to dominate. Thus, the essential elements of equilibrium in Keynesian theory, the financial theory of investment and the investment theory of business cycles, are most apt when examined as outcomes of processes that operate over time. During the 1980s, there was a sharp increase in speculative financing resulting from the trend toward leveraged buyouts and the rising demand for short-term marketable corporate liabilities. A main characteristic of a capitalist economy that is stagnant or immersed in a depression is that the capital development of the economy is not progressing. The 1980s were filled with examples of financing inept investments, while the current climate is one of grossly inadequate investment levels to create a progressive full-employment economy. The financial instability interpretation of Keynes rests upon the profitability of debt financing, and incorporates the potential collapse of asset values in an environment of speculative and Ponzi financing. Consequently, the financial structure is significantly more fragile today than earlier in the post World War II era.
Keywords: 330